Microalloyed magnesium alloy negative electrode material as well as preparation method and application thereof

By adding trace elements such as Gd, Ce and Mn to the magnesium battery negative electrode material and using multi-step process processing, a microalloy magnesium alloy negative electrode material with excellent electrochemical performance was prepared, which solved the problems of short cycle life and dendrite generation of magnesium battery negative electrode material, and achieved a longer cycle life and lower overpotential.

CN119710403AActive Publication Date: 2025-03-28CHONGQING UNIV +1

Patent Information

Application Number
CN202411969750.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The negative electrode material of existing magnesium ion batteries has short cycle life, and there are problems of dendrite generation and passivation film formation, which limits its ability to apply at high current density.

Method used

The negative electrode material with excellent electrochemical properties is prepared by adding trace elements such as Gd, Ce and Mn, and smelting, solid solution treatment, extrusion treatment, rolling treatment and annealing treatment.

Benefits of technology

The cycle stability and electrochemical performance of the negative electrode material of magnesium battery is significantly improved, the overpotential is reduced, the dendrite generation is suppressed, the cycle life of the battery is extended, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710403A_ABST
    Figure CN119710403A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium secondary battery electrode materials, in particular to a microalloyed magnesium alloy negative electrode material as well as a preparation method and application thereof, and the microalloyed magnesium alloy negative electrode material comprises the following components in percentage by mass: 0.01-2.0 wt.% of Gd and / or 0.01-2.0 wt.% of Ce, 0.01-1.0 wt.% of Mn and the balance of Mg. The preparation method comprises the following steps: weighing the raw materials according to the component proportion of the microalloyed magnesium alloy negative electrode material, smelting the raw materials, pouring, and carrying out air cooling solidification to obtain a cast ingot; the raw materials comprise pure Mg, an Mg-Gd intermediate alloy and an Mg-Mn intermediate alloy, or the raw materials comprise pure Mg, an Mg-Ce intermediate alloy and an Mg-Mn intermediate alloy; and sequentially carrying out solution treatment, extrusion treatment, rolling treatment and annealing treatment on the cast ingot to obtain the microalloyed magnesium alloy negative electrode material. The material is excellent in long cycle stability, low in overpotential, environment-friendly and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium secondary battery electrode materials, and in particular to a microalloyed magnesium alloy negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been unable to meet the growing social needs due to their high cost and poor safety. Rechargeable magnesium batteries are a new type of battery with great potential. They have a large theoretical volume capacity (3833mAh / cm 3 ), rich resources (the content in the earth's crust is about 104 times that of lithium), low reduction potential (reduction potential is -2.37V) and not easy to grow dendrites have attracted widespread attention.

[0003] An ideal negative electrode material needs to have a very high specific capacity and a low reaction voltage. Magnesium metal is an ideal negative electrode material. When magnesium was first used as a negative electrode for secondary batteries, it was considered to be dendrite-free, but this conclusion is highly dependent on the electrolyte and current density. Recent studies have shown that under fast charging or certain low temperature conditions, dendrites will grow on the surface of magnesium metal, and their hardness is even higher than that of lithium dendrites. In addition, in traditional electrolytes, a dense passivation film will form on the surface of magnesium metal to hinder the Mg 2+ The migration of magnesium anode and electrolyte causes voltage hysteresis and other problems. Due to the presence of passivation film, bulk magnesium metal is not suitable for some polar electrolytes. Therefore, in addition to improving magnesium electrolyte, efforts should also be made to improve the compatibility of magnesium negative electrode and electrolyte.

[0004] At present, domestic and foreign scholars' research on magnesium-ion batteries is mainly focused on positive electrode materials and electrolytes. Pure magnesium is generally used as the negative electrode material. There are few research reports on other negative electrode materials, especially binary alloys for rechargeable magnesium batteries. In addition, the various types of rechargeable magnesium battery alternative negative electrodes currently under research are limited in large-scale production and application due to their complex preparation processes and high costs. Summary of the invention

[0005] The purpose of the present invention is to provide a microalloyed magnesium alloy negative electrode material and a preparation method and application thereof, which has excellent long cycle stability, low overpotential, is environmentally friendly and has low cost.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a microalloyed magnesium alloy negative electrode material, which comprises the following components by mass percentage: 0.01-2.0 wt. % Gd and / or 0.01-2.0 wt. % Ce, 0.01-1.0 wt. % Mn, and the balance Mg.

[0008] Furthermore, the content of impurity elements in the microalloyed magnesium alloy negative electrode material is less than 0.05 wt.%.

[0009] In a second aspect, the present invention provides a method for preparing a microalloyed magnesium alloy negative electrode material, which comprises:

[0010] Weighing raw materials according to the component ratio of the microalloyed magnesium alloy negative electrode material according to claim 1 or 2, melting and pouring the raw materials, and air-cooling and solidifying them to obtain ingots; the raw materials include pure Mg, Mg-Gd master alloy and Mg-Mn master alloy, or the raw materials include pure Mg, Mg-Ce master alloy and Mg-Mn master alloy;

[0011] The ingot is subjected to solution treatment, extrusion treatment, rolling treatment and annealing treatment in sequence to obtain a micro-alloyed magnesium alloy negative electrode material.

[0012] Further, the raw materials are melted, poured, and air-cooled to solidify to obtain an ingot, which specifically includes: performing surface impurity removal treatment on the raw materials; placing a crucible in a smelting furnace and preheating it to 300-500° C., adding pure Mg to the crucible in a mixed protective atmosphere of CO2 and SF6, and continuing to heat it to 650-700° C.; after all the pure Mg is melted, heating it to 740-760° C., adding preheated Mg-Gd master alloy and Mg-Mn master alloy or Mg-Ce master alloy and Mg-Mn master alloy, skimming, and stirring until the master alloy is completely melted; stopping heating and keeping warm for 20-30 minutes, skimming, adding a refining agent, and stirring until the metal liquid surface presents a mirror surface to obtain a melt; standing the melt at a temperature of 740-760° C. for 20-30 minutes, skimming, and then pouring the melt into a mold, and air-cooling to solidify to obtain an ingot.

[0013] Furthermore, the inner wall of the crucible, the inner surface of the mold, and the parts of the skimming tool and stirring tool that contact the molten metal are evenly coated with boron nitride coating, and the crucible, the mold, the skimming tool and the stirring tool are preheated and dried at a temperature of 200°C to 300°C.

[0014] Furthermore, the solution treatment specifically includes: wrapping the ingot with aluminum foil, placing the ingot in a stainless steel crucible, and covering it with graphite powder to prevent oxidation, and then performing solution treatment in a heating furnace; the solution treatment temperature is set to 300-400°C, the solution treatment time is set to 8-24h, and the cooling method is water cooling.

[0015] Furthermore, the extrusion treatment specifically includes: machining the ingot after the solution treatment into an extrusion blank, and then extruding it at a temperature of 350-450°C.

[0016] Furthermore, the rolling treatment specifically includes: keeping the extruded slab obtained by the extrusion treatment at a temperature of 250-300°C for 10-30 minutes, and then rolling; the rolling passes are 3-5 times, and the plate reduction in each pass is set to 20-30%, and after each rolling pass, keeping it at a temperature of 250-300°C for 10-30 minutes.

[0017] Furthermore, the annealing temperature of the annealing treatment is set to 300-400° C., and the annealing time is set to 10-30 min.

[0018] In a third aspect, the present invention provides a use of the above-mentioned microalloyed magnesium alloy negative electrode material in a negative electrode of a magnesium battery.

[0019] The present invention has the following unexpected beneficial effects:

[0020] 1. In view of the short cycle life of pure magnesium negative electrode, the present invention prepares a microalloyed ternary magnesium alloy for magnesium secondary battery negative electrode material by melting, solution treatment, extrusion treatment, rolling treatment and annealing treatment of high-purity Mg, Mn and Gd and / or Ce in a certain mass ratio. Compared with pure magnesium, the polarization overpotential at different current densities is lower and the dissolution / deposition stability during the cycle is better. At the same time, the microalloyed magnesium alloy negative electrode material can effectively inhibit the formation of dendrites at the interface, so that it still has a longer cycle life at a higher current density.

[0021] 2. The preparation method of the present invention has a simple process. The addition of trace alloy elements not only improves the electrochemical properties of pure magnesium, but also makes the magnesium alloy negative electrode material have better processing properties. At the same time, the cost is low, and it can be applied to large-scale industrial production, with better application prospects.

[0022] 3. The main raw material magnesium described in the present invention is abundant and easy to obtain, and the amount of added elements is small, which has little impact on the ecological environment and avoids a large amount of dependence on scarce resources; the excellent electrochemical properties of the alloy significantly improve the cycle life of the battery, which can reduce the waste of resources caused by frequent replacement and the environmental burden of discarded batteries; at the same time, its preparation and use process does not involve highly toxic chemicals, has high safety, and avoids the risk of thermal runaway and environmental pollution of lithium-ion batteries; in addition, magnesium alloys are easy to recycle, and the degradation process is harmless to the ecosystem, which helps to promote the popularization of green energy storage and the development of a circular economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the process of preparing the microalloyed magnesium alloy negative electrode material of the present invention;

[0024] Figure 2 The current density is 0.3 mA cm -2-0.3mAh·cm -2 The charge and discharge curves of pure magnesium, Mg-Mn, Mg-Gd and Mg-Gd-Mn symmetric batteries in the APC electrolyte system with a concentration of 0.4M under the conditions;

[0025] Figure 3 The current density is 0.3 mA cm -2 -0.3mAh·cm -2 Voltage relaxation diagrams of pure magnesium, Mg-Mn, Mg-Gd and Mg-Gd-Mn symmetric cells in an APC electrolyte system with a concentration of 0.4 M under different conditions;

[0026] Figure 4 The current density is 3 mA cm -2 -3mAh·cm -2 The charge and discharge curves of pure magnesium, Mg-Mn, Mg-Gd and Mg-Gd-Mn symmetric batteries in the APC electrolyte system with a concentration of 0.4M under the conditions;

[0027] Figure 5 The current density is 0.3 mA cm -2 -0.3mAh·cm -2 Schematic diagram of the comparison of the Coulombic efficiency of pure Mg, Mg-Mn, Mg-Gd and Mg-Gd-Mn half-cells after 200 cycles in an APC electrolyte system with a concentration of 0.4 M under the same conditions;

[0028] Figure 6 The current density is 3 mA cm -2 -3mAh·cm -2 Charge and discharge curves of pure magnesium, Mg-Mn, Mg-Ce and Mg-Ce-Mn symmetric batteries in an APC electrolyte system with a concentration of 0.4M under certain conditions.

[0029] Figure 7 The current density is 3 mA cm -2 -5mAh·cm -2 The charge and discharge curves of pure magnesium, Mg-Mn, Mg-Ce and Mg-Ce-Mn symmetric batteries in the first 20 hours in the APC electrolyte system with a concentration of 0.4M under certain conditions. DETAILED DESCRIPTION

[0030] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0031] In one embodiment, the present invention provides a microalloyed magnesium alloy negative electrode material, which includes the following components by mass percentage: 0.01-2.0wt.% Gd and / or 0.01-2.0wt.% Ce, 0.01-1.0wt.% Mn, and the balance is Mg.

[0032] The present invention, by rationally selecting alloy elements and optimizing alloy composition, has lower polarization overpotentials at different current densities and better dissolution and deposition stability during the cycle process than pure magnesium. Compared with lithium metal negative electrodes, magnesium metal negative electrodes are not easy to form dendrites during the electrodeposition process, and microalloying further inhibits the growth of magnesium dendrites, so that it still has a longer cycle life at a higher current density, avoids the problem of dendrites penetrating the diaphragm to cause battery short circuit, and improves the safety and cycle stability of the battery. In addition, the addition of trace alloy elements (Mn and Gd and / or Ce) can refine the grains of the magnesium alloy, enhance its matrix strength and hardness, enable the negative electrode material to better maintain the integrity of the electrode structure during the charge and discharge process, reduce the pulverization and shedding of the electrode material, thereby improving the cycle life and stability of the battery.

[0033] In a preferred embodiment, the content of impurity elements in the microalloyed magnesium alloy negative electrode material is less than 0.05wt%. By reducing the content of impurity elements, the occurrence of adverse side reactions can be reduced, thereby improving the electrochemical performance of the battery, such as increasing energy density, extending cycle life and enhancing stability.

[0034] The reduction of impurity elements helps maintain the homogeneity and integrity of the material, thereby improving its mechanical properties, such as increasing toughness, reducing brittleness and improving fatigue resistance.

[0035] Strict control of impurity elements can also reduce defects and failures that may occur during material processing and use, thereby improving product reliability and safety.

[0036] The content of impurity elements is controlled by the following means.

[0037] 1) Raw material selection: Selecting high-purity raw materials is key to reducing the content of impurity elements. This includes ensuring that the raw materials for magnesium, rare earth elements and transition metal elements are of high purity and avoiding the use of recycled materials that contain a lot of impurities.

[0038] 2) Production process optimization: During the smelting and casting process, take appropriate measures to reduce the introduction of impurities, such as using inert gas protection, controlling smelting temperature and time, and adopting effective impurity removal processes.

[0039] 3) Quality testing and monitoring: Strict quality testing and monitoring are carried out on each link of the production process to ensure that the impurity element content of the final product meets the specified requirements.

[0040] In one embodiment, the present invention provides a method for preparing a microalloyed magnesium alloy negative electrode material, see Figure 1 As shown, the preparation method comprises:

[0041] The raw materials are weighed according to the component proportions of the microalloyed magnesium alloy negative electrode material described in the above embodiment, and the raw materials are melted, poured, and air-cooled to solidify to obtain an ingot; the raw materials include pure Mg, Mg-Gd master alloy and Mg-Mn master alloy, or the raw materials include pure Mg, Mg-Ce master alloy and Mg-Mn master alloy.

[0042] The ingot is subjected to solution treatment, extrusion treatment, rolling treatment and annealing treatment in sequence to obtain a micro-alloyed magnesium alloy negative electrode material.

[0043] The preparation method of the present invention has the advantages of simple process, easy control, low cost, etc., is suitable for large-scale industrial production, and has good application prospects.

[0044] In a preferred embodiment, the process of melting and pouring the raw materials and solidifying them by air cooling to obtain an ingot specifically includes:

[0045] The raw materials are treated to remove impurities from the surface to prevent these impurities from entering the melt during the smelting process and affecting the performance of the final material. The raw materials can be treated to remove impurities from the surface by mechanical grinding, pickling, alkali washing, etc.

[0046] Preheat the crucible to 300-500°C in a melting furnace. The purpose of preheating the crucible is to reduce the heat absorption of the melt by the crucible during the melting process and to prevent the crucible from breaking due to rapid temperature rise. Add pure Mg to the crucible in a mixed protective atmosphere of CO2 and SF6, and continue to heat it to 650-700°C; after all the pure Mg is melted, heat it to 740-760°C, add the preheated Mg-Gd master alloy and Mg-Mn master alloy or Mg-Ce master alloy and Mg-Mn master alloy, skim the slag, and stir until the master alloy is completely melted.

[0047] Stop heating and keep warm for 20-30 minutes to make the composition of the melt more uniform. Skim the slag again and then add the refining agent. The refining agent can remove the gas and fine impurities in the melt and improve the purity of the melt. Stir until the metal surface is mirror-like, indicating that the melt has been fully refined. Let the melt stand at a temperature of 740-760℃ for 20-30 minutes to allow the impurities and gases in the melt to float and separate further.

[0048] The melt is left to stand for 20 to 30 minutes at a temperature of 740 to 760°C, the slag is skimmed, and then the melt is poured into a mold and air-cooled to solidify to obtain an ingot. The air-cooling solidification speed is relatively slow, which is conducive to more uniform composition and structure in the ingot.

[0049] Furthermore, the inner wall of the crucible, the inner surface of the mold, and the parts of the skimming tool and stirring tool that contact the molten metal are evenly coated with boron nitride coating, and the crucible, the mold, the skimming tool and the stirring tool are preheated and dried at a temperature of 200°C to 300°C.

[0050] Boron nitride (BN) coating has excellent high temperature resistance, corrosion resistance and lubricity. Applying it on the inner wall of the crucible, the inner surface of the mold, and the parts where the skimming tool and stirring tool contact the molten metal can effectively prevent these parts from being corroded or adhered by the molten metal at high temperatures, while reducing the friction between the molten metal and these parts, and improving the smoothness of the smelting and pouring process.

[0051] Painting method: Make sure the paint is evenly applied on the surface of these parts to form a continuous and dense coating. Before painting, clean the surface of these parts to remove oil, impurities, etc. to ensure good bonding between the paint and the substrate.

[0052] Preheating and drying crucibles, molds, slag skimming tools and stirring tools at a temperature of 200℃ to 300℃ can remove moisture and adsorbed gas on the surface of these tools, and prevent quality problems such as splashing and pores caused by moisture evaporation or gas release during smelting and pouring. At the same time, preheating can also reduce the temperature difference between these tools and high-temperature molten metal, and prevent thermal stress cracks caused by rapid temperature rise.

[0053] Preheating method: Place the crucible, mold, skimming tool and stirring tool in the preheating furnace, heat to the specified temperature and maintain for a period of time to ensure that the temperature inside and outside of these tools is uniform. The preheating time should be adjusted according to the size and material of the tool.

[0054] In a preferred embodiment, the solution treatment specifically includes:

[0055] Aluminum foil coating: First, the ingot is coated with aluminum foil. Aluminum foil has good sealing and corrosion resistance, which effectively prevents the ingot from direct contact with oxygen in the air during the solution treatment process, thereby avoiding the occurrence of oxidation reactions. At the same time, aluminum foil can also serve as a buffer layer to reduce the thermal stress of the ingot during heating and cooling.

[0056] Stainless steel crucible placement: Place the coated ingot in a stainless steel crucible. The stainless steel crucible has good high temperature resistance and chemical stability, and can withstand the high temperature environment during the solution treatment process while preventing the ingot from reacting with the crucible material.

[0057] Graphite powder covering: A layer of graphite powder is covered on the ingot. Graphite powder has good thermal conductivity and chemical inertness, which further prevents the oxidation reaction of the ingot during the solution treatment process, while helping to evenly transfer heat and improve the efficiency of the solution treatment.

[0058] Heating furnace solid solution treatment: Place the stainless steel crucible containing the ingot into the heating furnace for solid solution treatment. The solid solution treatment temperature is set at 300-400°C and the solid solution treatment time is set at 8-24 hours. This combination of temperature and time is to ensure that the alloy elements are fully dissolved in the magnesium matrix to form a uniform solid solution, thereby improving the performance of the material.

[0059] Water cooling: After the solution treatment is completed, the ingot is quickly cooled by water cooling. Water cooling can quickly reduce the temperature of the ingot and prevent the alloy elements from re-precipitating during the cooling process, thereby maintaining the uniformity of the solid solution. At the same time, water cooling can also reduce the thermal stress of the ingot during the cooling process and avoid defects such as cracks.

[0060] In a preferred embodiment, the extrusion treatment specifically includes: machining the solution treated ingot into an extrusion blank to remove surface defects such as oxide scale and inclusions, and adjusting its shape and size to meet the requirements of the extruder. During the processing, the dimensional accuracy and surface quality of the blank need to be ensured to avoid defects such as cracks and folds during the extrusion process.

[0061] Then, extrusion is carried out at a temperature of 350-450°C. This temperature is determined according to the extrusion characteristics and required properties of the magnesium alloy, aiming to ensure that the alloy has good plasticity and fluidity during the extrusion process while avoiding coarsening of the structure and degradation of performance due to overheating.

[0062] In a preferred embodiment, the rolling process specifically includes: keeping the extruded slab obtained by the extrusion process at a temperature of 250-300°C for 10-30 minutes to make the internal temperature of the slab uniform, reduce the thermal stress during the rolling process, and improve the plasticity and fluidity of the material, which is beneficial to the subsequent rolling operation. Then rolling is carried out, the rolling passes are 3-5 times, and the plate reduction amount in each pass is set to 20-30%. A reasonable reduction amount helps to obtain a uniform microstructure and good mechanical properties. After each rolling pass, keep it at a temperature of 250-300°C for 10-30 minutes. The internal stress of the plate is released by heating and heat preservation treatment, and the plasticity of the material is restored to prepare for the next rolling pass.

[0063] In a preferred embodiment, the annealing temperature of the annealing treatment is set to 300-400° C. At this temperature, the residual stress in the magnesium alloy can be effectively released while avoiding grain growth and performance degradation caused by excessively high temperatures.

[0064] The annealing time is set to 10 to 30 minutes. The length of the annealing time directly affects the microstructure and performance of the material. Too short an annealing time may not be able to fully release the residual stress, affecting the performance of the material; too long an annealing time may cause grain growth and reduce the strength and hardness of the material.

[0065] In one embodiment, the present invention provides an application of the microalloyed magnesium alloy negative electrode material described in any one of the above embodiments in a negative electrode of a magnesium battery.

[0066] The present invention is analyzed and explained below with reference to specific examples.

[0067] Embodiment 1, a method for preparing a microalloyed magnesium alloy negative electrode material, comprising the following steps:

[0068] Step 1: Preparation of magnesium alloy ingots

[0069] Under the protection of a mixed gas of CO2 and SF6, pure magnesium ingots and intermediate alloys are melted in order according to the proportions to obtain alloy melts, slag skimming is performed and refining agents are added, and finally, cast alloys are cast under a protective atmosphere.

[0070] The specific steps include:

[0071] A. Preparation of furnace charge and equipment: Use electric polisher to remove oxides on the surface of pure magnesium ingot (99.99wt.%) and intermediate alloy (Mg-30wt.%Gd, Mg-5wt.%Mn), so that the charge is free of mildew, rust, oil stain, etc., and then cut into small pieces for use. The surfaces of stirring tools, casting molds, crucibles, etc. that come into contact with the melt are coated with a coating of boron nitride and alcohol mixed in a volume ratio of 1:4, and preheated at a temperature of 200-300℃ for at least 30 minutes.

[0072] B. Ingredients: Considering that the burnout of the trace amount of Gd added is 10% to 15%, the burnout of Mn is about 25%, and about 3 kg of alloy is smelted each time, the amount of master alloy required for the Mg-Gd-Mn alloy to be melted is shown in Table 1.

[0073] Table 1 The amount of master alloy required for smelting Mg-1.0Gd-0.3Mn alloy

[0074]

[0075] C. Melting: Preheat the crucible to dark red (about 500℃), add a fixed amount of pure magnesium ingot, and introduce a mixed protective gas of CO2 and SF6, where the volume ratio of the mixed protective gas of CO2 and SF6 is: Continue to heat and melt; heat to 650℃ until the magnesium ingot is completely melted. Then heat to 740℃, add the preheated quantitative intermediate alloy, deslagging after adding, stirring for 2 to 3 minutes until completely melted, and promote the dissolution and dispersion of alloy elements. Add other alloys in the same way (the order of addition is Mg-30Gd, Mg-5Mn), and each time the raw materials are added, the protective gas needs to be continuously introduced and the heating power is turned off. After confirming that the metal is melted, skim off the surface scum, add JDMJ refining agent and refine for 3 to 5 minutes, that is, add the refining agent while stirring.

[0076] D. Pouring: The melt is allowed to stand for 20 minutes at a temperature of 740°C before pouring. Before pouring, the slag is removed to remove the oxides on the surface of the melt, and then the melt is poured into a preheated (200-300°C) cast iron mold. Finally, the Mg-1.0Gd-0.3Mn alloy ingot is obtained by air cooling and demolding.

[0077] Step 2, solution treatment: use a heat treatment furnace for solution treatment, heat the heat treatment furnace to 400°C, place the alloy ingot in the heat treatment furnace, keep it warm for 24 hours, take it out and water cool it to obtain a solid solution magnesium alloy ingot. That is, the heat treatment parameters of the solution treatment are 400°C×24h, water cooling.

[0078] Step three, preparation of extruded slabs: surface treatment of the solid solution magnesium alloy ingot, grinding off the surface oxide film, and preheating the solid solution magnesium alloy ingot in an insulating environment at a temperature of 400°C for 30 minutes. The temperature during the extrusion process is 400°C, and the extrusion ratio is 47:1, and finally a Mg-1.0Gd-0.3Mn magnesium alloy slab with a thickness of 2 mm is obtained.

[0079] Step 4, preparation of rolled plate: the cross-sectional size of the extruded plate used for rolling is 60 mm×2 mm, and the rolling is carried out at a temperature of 250° C. and is kept in a heat preservation environment at 250° C. for 30 minutes before rolling.

[0080] After each rolling pass, the plate was kept at 250° C. for 10 minutes, and the plate reduction was kept constant at 30%. Three rolling passes were performed in total, and the thickness of the final Mg-1.0Gd-0.3Mn plate was about 0.7 mm.

[0081] Step 5, preparation of electrode sheet: annealing a magnesium alloy sheet with a thickness of about 0.7 mm, setting the annealing temperature to 400°C, and setting the holding time to 10 min. After annealing, use a slicer to cut a magnesium alloy negative electrode sheet with a diameter of 14 mm. Then use sandpaper to polish to 3000 mesh to remove the oxide layer of the material. The thickness of the polished magnesium alloy negative electrode sheet is 0.3-0.5 mm. Then place it in alcohol for ultrasonic cleaning for 10 min, dry it in a vacuum drying oven for 12 h, and put it in an argon glove box with a water and oxygen value of less than 1 ppm for standby use.

[0082] Electrochemical analysis: In a glove box filled with argon, the prepared magnesium alloy was used as the pole piece, GF / A glass fiber was used as the diaphragm, and APC with a concentration of 0.4M was used as the electrolyte to assemble the CR2032 button cell. The assembly order of the symmetrical battery is: negative electrode shell, alloy negative electrode sheet, diaphragm, alloy negative electrode sheet, gasket, spring sheet and positive electrode shell. For the half-battery assembly, the pole piece on one side of the positive electrode shell was replaced with a Φ12mm copper foil, and the rest remained unchanged. The above-mentioned battery shell, copper foil, gasket and shrapnel were ultrasonically cleaned twice in deionized water for twenty minutes each time, and then placed in a blast drying oven for drying. The diameter of the diaphragm was Φ17mm, and the amount of electrolyte used each time was 100μL. After the assembly was completed, the battery was placed on an automatic sealing machine for compaction. After the battery assembly was completed, it was left to stand for 12 hours to ensure that the electrolyte completely infiltrated the electrode. The electrochemical test was completed in a 30℃ constant temperature box using the Xinwei battery test system, and the battery was charged and discharged by controlling the charge and discharge current, time and charge cut-off voltage.

[0083] The difference between Example 2 and Example 1 is that the raw materials are 2708.2g pure magnesium, 240g Mg-5Mn and 56.8g Mg-30Ce metal blocks, and the final negative electrode material obtained is Mg-0.5wt.%Ce-0.3wt.%Mn alloy.

[0084] The difference between Comparative Example 1 and Example 1 is that the raw material is only 3000.0 g of pure magnesium metal block, and the negative electrode material finally obtained is pure Mg.

[0085] Comparative Example 2 is different from Example 1 in that the raw materials are 2763.0 g of pure magnesium metal block and 240.0 g of Mg-5Mn metal block, and the negative electrode material finally obtained is Mg-0.3 wt. % Mn alloy.

[0086] Comparative Example 3 is different from Example 1 in that the raw materials are 2890.5 g of pure magnesium metal block and 113.6 g of Mg-30Gd metal block, and the final negative electrode material is Mg-1.0 wt.% Gd alloy.

[0087] Comparative Example 4 is different from Example 1 in that the raw materials are 2945.2 g of pure magnesium metal block and 56.8 g of Mg-30Ce metal block, and the final negative electrode material obtained is Mg-0.5wt.%Ce alloy.

[0088] The test results are detailed in the attached Figures 2 to 7 .

[0089] Depend on Figure 2 and Figure 3 It can be seen that at 0.3 mA cm -2 During the long-term charge and discharge cycle within 500h under the same conditions, the overpotentials of the symmetrical batteries in Example 1 and the corresponding three comparative examples are Mg-Mn, Mg, Mg-Gd, and Mg-Gd-Mn from large to small, and the ternary micro-alloyed Mg-Gd-Mn alloy has a lower overpotential (0.04V), indicating that the synergistic effect of trace Gd and Mn is beneficial to improving the uniformity and kinetics of magnesium deposition / dissolution and weakening the polarization phenomenon at the interface between the metal magnesium negative electrode and the electrolyte.

[0090] Depend on Figure 4 It can be seen that at 3mA·cm -2 At this relatively high current density, the symmetrical battery of Example 1 and the three comparative examples has the longest cycle time of Mg-Gd-Mn, with a cycle life of 1054 h. This indicates that the ternary microalloyed Mg-Gd-Mn still has excellent deposition / dissolution stability at this current density, showing the best cycle stability and anti-polarization ability.

[0091] Figure 5The Coulombic efficiency of the first and third comparative half-cells in the first 200 cycles is shown. Compared with pure Mg and the other two alloys (Mg-Mn and Mg-Gd), the Coulombic efficiency of the ternary Mg-Gd-Mn reaches 100% earlier and has an average Coulombic efficiency of 99.3% in the first 200 cycles.

[0092] Figure 6 For Example 2 and the corresponding three comparative examples at 3 mA·cm -2 The charge-discharge curve under this relatively large current density shows the same rule as that of Example 1, that is, the longest cycle life is that of the ternary microalloyed Mg-Ce-Mn (over 1100 h). Figure 7 As shown, the charge and discharge surface capacity is further increased to 5 mAh cm -2 When , the ternary microalloyed Mg-Ce-Mn still exhibits the lowest nucleation overpotential and polarization voltage.

[0093] Note that the standard electrode potentials of Gd (-2.40) and Ce (-2.34) are similar to that of Mg (-2.37). The test results of Mg-Gd and Mg-Ce show that the introduction of trace alloy elements with similar electrode potentials can greatly extend the battery cycle life. At the same time, the electrochemical test results of the two embodiments of Mg-Gd-Mn and Mg-Ce-Mn show that the introduction of trace Mn to form a ternary alloy can further extend the battery cycle life, which shows that Mn can synergistically interact with Gd and Ce to improve the electrochemical performance of the magnesium negative electrode.

[0094] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A microalloyed magnesium alloy negative electrode material, characterized in that: The composition includes the following components by mass percentage: 0.01-2.0 wt. % of Gd and / or 0.01-2.0 wt. % of Ce, 0.01-1.0 wt. % of Mn, and the balance is Mg.

2. The microalloyed magnesium alloy negative electrode material according to claim 1, characterized in that: The content of impurity elements in the microalloyed magnesium alloy negative electrode material is less than 0.05 wt.%.

3. A method for preparing a microalloyed magnesium alloy negative electrode material, characterized in that: include: Weighing raw materials according to the component ratio of the microalloyed magnesium alloy negative electrode material according to claim 1 or 2, melting and pouring the raw materials, and air-cooling and solidifying them to obtain ingots; the raw materials include pure Mg, Mg-Gd master alloy and Mg-Mn master alloy, or the raw materials include pure Mg, Mg-Ce master alloy and Mg-Mn master alloy; The ingot is subjected to solution treatment, extrusion treatment, rolling treatment and annealing treatment in sequence to obtain a micro-alloyed magnesium alloy negative electrode material.

4. The method for preparing a microalloyed magnesium alloy negative electrode material according to claim 3, characterized in that: The raw materials are melted, poured, and air-cooled to solidify to obtain an ingot, which specifically includes: Carry out surface impurity removal treatment on the raw materials; Preheat the crucible in a melting furnace to 300-500°C, add pure Mg into the crucible in a mixed protective atmosphere of CO2 and SF6, and continue to heat it to 650-700°C; after all the pure Mg is melted, heat it to 740-760°C, add the preheated Mg-Gd master alloy and Mg-Mn master alloy or Mg-Ce master alloy and Mg-Mn master alloy, skim the slag, and stir until the master alloy is completely melted; Stop heating and keep warm for 20-30 minutes, skim the slag, add refining agent, and stir until the metal surface becomes mirror-like to obtain a melt; The melt is allowed to stand at a temperature of 740-760°C for 20-30 minutes, the slag is skimmed, and then the melt is poured into a mold and solidified by air cooling to obtain an ingot.

5. The method for preparing a microalloyed magnesium alloy negative electrode material according to claim 4, characterized in that: The inner wall of the crucible, the inner surface of the mold, and the parts of the skimming tool and the stirring tool that are in contact with the molten metal are evenly coated with boron nitride coating, and the crucible, the mold, the skimming tool and the stirring tool are preheated and dried at a temperature of 200°C to 300°C.

6. The method for preparing a microalloyed magnesium alloy negative electrode material according to claim 3, characterized in that: The solution treatment specifically includes: wrapping the ingot with aluminum foil, placing the ingot in a stainless steel crucible, and covering it with graphite powder to prevent oxidation, and then performing the solution treatment in a heating furnace; the solution treatment temperature is set to 300~400℃, the solution treatment time is set to 8~24h, and the cooling method is water cooling.

7. The method for preparing a microalloyed magnesium alloy negative electrode material according to claim 3, characterized in that: The extrusion treatment specifically includes: machining the ingot after the solution treatment into an extrusion blank, and then extruding it at a temperature of 350-450°C.

8. The method for preparing a microalloyed magnesium alloy negative electrode material according to claim 3, characterized in that: The rolling process specifically includes: keeping the extruded slab obtained by the extrusion process at a temperature of 250-300° C. for 10-30 minutes, and then rolling; The rolling passes are 3 to 5 times, and the plate reduction in each pass is set at 20 to 30%. After each rolling pass, the plate is kept warm at 250 to 300°C for 10 to 30 minutes.

9. The method for preparing a microalloyed magnesium alloy negative electrode material according to claim 3, characterized in that: The annealing temperature of the annealing treatment is set to 300~400℃, and the annealing time is set to 10~30min.

10. Use of the microalloyed magnesium alloy negative electrode material according to claim 1 or 2 in a negative electrode of a magnesium battery.

Citation Information

Patent Citations

  • High thermal conductivity magnesium alloy used under high temperature and preparation method thereof

    CN104651689A

  • Preparation method for magnesium alloy negative electrode material used for seawater battery

    CN105755338A

  • Magnesium alloy for magnesium battery negative electrode material and preparation method

    CN115584421A

  • Ce-containing magnesium alloy sacrificial anode and preparation method and application thereof

    CN116180092A

  • High-corrosion-resistance low-rare-earth magnesium alloy and preparation method thereof

    CN117385246A

Cited By

  • Preparation method of flexible alloy negative electrode with embedded structure

    CN120637404A

  • Magnesium alloy negative electrode material with porous structure as well as preparation method and application of magnesium alloy negative electrode material

    CN121272248A

  • Multi-type twin crystal defect magnesium alloy negative electrode material and preparation method thereof

    CN121905838A